PERFORMANCE AND FACTORS THAT INFLUENCE IT - Felix Chandra; Nurul Maghfirah (SEAN Institute, 2023)
This research aims to determine the influence of work discipline and career development on employee performance. This type of research is explanatory. This research was conducted on Everbright Hotel employees. The population in this study was 30 people. The sample used was 30 people using a saturated sampling technique, namely taking the entire population as a sample. The measurement scale used is the Likert scale. The data in this research was collected by distributing questionnaires to respondents. The data analysis technique used to test the hypothesis is multiple regression with the help of SPSS tools. The research results show that work discipline has a positive and significant effect on employee performance and career development has no effect on employee performance.